1998
DOI: 10.1126/science.279.5349.384
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the HIV-1 Nucleocapsid Protein Bound to the SL3 Ψ-RNA Recognition Element

Abstract: The three-dimensional structure of the human immunodeficiency virus-type 1 (HIV-1) nucleocapsid protein (NC) bound to the SL3 stem-loop recognition element of the genomic Psi RNA packaging signal has been determined by heteronuclear magnetic resonance spectroscopy. Tight binding (dissociation constant, approximately 100 nM) is mediated by specific interactions between the amino- and carboxyl-terminal CCHC-type zinc knuckles of the NC protein and the G7 and G9 nucleotide bases, respectively, of the G6-G7-A8-G9 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

45
813
1
4

Year Published

1998
1998
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 640 publications
(865 citation statements)
references
References 64 publications
45
813
1
4
Order By: Relevance
“…The case of human immunodeficiency virus type 1 (HIV-1) may somewhat be similar to MMTV: the 5ʹ UTR in HIV-1 implicated in RNA packaging folds into several stem loops, SL1-4 [39,40] of which SL1 harbors a GC-rich 6-nt pal sequence in the form of a loop that has been shown to function as the DIS [41,42]. Until recently SL3, which is present downstream of mSD, had been proposed to be the main HIV-1 packaging signal since it harbors a conserved region containing a GGAG tetraloop that has been shown to bind NC [43]. However, it has now been shown that SL1, in addition to containing the HIV-1 DIS, also harbors a single-stranded purine rich internal loop (ssPurine: GAGG) that acts as the main site for HIV-1 Gag binding during gRNA packaging [26,30,44,45].…”
Section: Discussionmentioning
confidence: 99%
“…The case of human immunodeficiency virus type 1 (HIV-1) may somewhat be similar to MMTV: the 5ʹ UTR in HIV-1 implicated in RNA packaging folds into several stem loops, SL1-4 [39,40] of which SL1 harbors a GC-rich 6-nt pal sequence in the form of a loop that has been shown to function as the DIS [41,42]. Until recently SL3, which is present downstream of mSD, had been proposed to be the main HIV-1 packaging signal since it harbors a conserved region containing a GGAG tetraloop that has been shown to bind NC [43]. However, it has now been shown that SL1, in addition to containing the HIV-1 DIS, also harbors a single-stranded purine rich internal loop (ssPurine: GAGG) that acts as the main site for HIV-1 Gag binding during gRNA packaging [26,30,44,45].…”
Section: Discussionmentioning
confidence: 99%
“…Structures of NC in complex with two of the isolated stem loops from HIV-1 Ψ show that the CCHC zinc fingers of NC make sequence-specific, but remarkably different, contacts with exposed loop residues (Fig. 2h) [85,86]. The NC/RNA interactions visualized in these structures undoubtedly contribute to the specificity of genomic RNA packaging, although the full mechanism by which HIV-1 Gag packages dimeric RNA genomes has yet to be delineated.…”
Section: Gag-gag Lattice Interactions In the Immature Virion Are Medimentioning
confidence: 99%
“…The monomers are shown in blue green and gray, and the MHR element in yellow. (g, h) Secondary structure of the HIV-1 Ψ packaging element (g), and high-resolution structures (h) of the isolated NC domain bound to the second (left) and third (right) Ψ stem loops, with NC in blue and RNA in red [85,86]. Color coding is the same as in (a), except with CA residues colored red to denote sites of significant protection from deuterium exchange in the hexagonal CA lattice [103].…”
Section: Virus Assembly In Vitro and In Vivomentioning
confidence: 99%
“…NC binds preferentially to ssDNA, although dsDNA binding is also very strong. This nucleic acid binding is believed to involve the partial stacking of the aromatic residues Phe16 and Trp37 in the zinc finger domains with unpaired nucleic acid bases, 120,121 and is known to be strongly salt dependent. 122,123 During the life cycle of the virus, NC acts as both a nucleic acid binding domain and a nucleic acid chaperone.…”
Section: Figure 11mentioning
confidence: 99%